2012
DOI: 10.1038/jid.2011.448
|View full text |Cite
|
Sign up to set email alerts
|

Epitope Spreading Is Rarely Found in Pemphigus Vulgaris by Large-Scale Longitudinal Study Using Desmoglein 2–Based Swapped Molecules

Abstract: Epitope spreading is involved in inducing and maintaining self-reactivity. Epitope spreading in pemphigus vulgaris (PV), caused by IgG autoantibodies to desmoglein 3 (Dsg3) and Dsg1, was previously analyzed using Dsg3/Dsg1 extracellular domain-swapped molecules. However, precise identification of the responsible epitopes in each molecule by using only this method was problematic. In this study, we studied epitope spreading in PV by a novel immunoprecipitation-immunoblot method using Dsg3 (or Dsg1)/Dsg2 domain-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
60
2
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 47 publications
9
60
2
4
Order By: Relevance
“…We further characterized the Dsg3 epitopes recognized by the isolated antibodies by immunoprecipitation/immunoblotting using a series of Dsg3/Dsg2 domain-swapped molecules produced using a baculovirus expression system (Ohyama et al, 2012). PNP-A1 bound to the EC3 domain of Dsg3, whereas PNP-B1 and PNP-C1 bound to the EC2 domain ( Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We further characterized the Dsg3 epitopes recognized by the isolated antibodies by immunoprecipitation/immunoblotting using a series of Dsg3/Dsg2 domain-swapped molecules produced using a baculovirus expression system (Ohyama et al, 2012). PNP-A1 bound to the EC3 domain of Dsg3, whereas PNP-B1 and PNP-C1 bound to the EC2 domain ( Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
“…To determine the epitopes of the PNP patient, as well as the scFvs, we used the following baculovirus-produced recombinant human Dsg3/Dsg2 domain-swapped molecules tagged with an E-tag and a histidine tag: Dsg3-EC1 (1-101), Dsg3-EC2 (95-221), Dsg3-EC3 (212-328), Dsg3-EC4 (320-440), and Dsg3-EC5 (440-551; Ohyama et al, 2012). Baculovirus-infected insect cell culture supernatants containing recombinant molecules were incubated with the serum or scFvs for 30 minutes, and then immunoprecipitated with protein G Sepharose 4 Fast Flow beads (GE Healthcare Bio-Sciences) for serum or anti-HA agarose (Sigma-Aldrich, St Louis, MO) for scFvs (at 4 1C overnight with gentle rotation).…”
Section: Epitope Mapping By Immunoprecipitation/immunoblottingmentioning
confidence: 99%
“…Genetic and ethnic factors explain part of these observations [13], and other autoantibodies, such as anti-desmocollin or anti-acetylcholine receptor, are known to be involved in pemphigus pathophysiology [26,27]. Isolated cases of phenotypic and immunological transition from PV to PF or vice versa were described [28,29], but epitope spreading may not be implicated [30,31]. Furthermore, commercial Dsg ELISA kits detect only IgG autoantibodies, but IgA and IgE are known to be involved [27,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal epitope-mapping studies of PV sera have shown that the targeted epitopes in DSG3 stay the same during active disease and relapse (63). Epitope spreading therefore appears to be a rare event, underscoring the static nature of the DSG3-reactive B cell repertoire in PV.…”
Section: Current Pv Treatment and Implications For The Development Ofmentioning
confidence: 99%
“…Based on the knowledge that the amino-terminal epitopes of DSG3 are predominantly targeted by PV autoantibodies (11,63), a tandem cyclic peptide consisting of DSG1 residues 81-87, highly homologous to the comparable DSG3 adhesive domain, was synthesized and shown to stabilize the trans-adhesive interface of both DSG3 and DSG1, thereby preventing autoantibody-mediated disruption of desmosomes (30,65). This treatment was effective in preventing keratinocyte pathology in vitro and also epidermal blistering when applied topically in vivo.…”
Section: Autoantibody Targeting Strategiesmentioning
confidence: 99%